Doping strategies towards acceptor-doped barium zirconate compatible with nickel oxide anode substrate subjected to high temperature co-sintering. (22nd May 2023) - Li, Yifeng; Guo, Shihang; Han, Donglin
Abstract: Protonic ceramic fuel cells (PCFCs) are attractive next-generation fuel cells working at intermediate temperature (450–700 °C). Currently, the most common method to produce PCFCs is based on co-sintering anode-supported half cells composed of thin BaZr0.8 Y0.2 O3-δ (BZY20) electrolyte layers and thick NiO anode substrates. However, the BZY20 electrolyte reacts with NiO at the high temperature during co-sintering (1400–1600 °C), leading to significant loss of dopants in the electrolyte and thereby degradation in the conductivity. With the aim to improve the chemical compatibility between the BaZrO3 -based electrolyte and NiO, in this work, we annealed the mixture of NiO and BaZrO3 doped with different dopants, and found that good compatibility was obtained between NiO and BaZr0.8 Yb0.2 O3-δ or BaZr0.8 Tm0.2 O3-δ at 1500 °C, and NiO and BaZr0.8 Yb0.2 O3-δ at 1350 °C. Furthermore, BaZr0.8 Y0.1 Yb0.1 O3-δ and BaZr0.8 Y0.12 Yb0.08 O3-δ also showed good chemical compatibility with NiO at 1350 and 1500 °C. Then, the half cells using the BaZrO3 electrolyte doped with Y and Yb were fabricated, and the ionic conductivities of the electrolytes implemented into the co-sintered half cells were measured directly in wet hydrogen. The results revealed that BaZr0.8 Y x Yb0.2- x O3-δ ( x = 0.10, 0.12, 0.13) showed higher conductivity than that of BaZr0.8 Y0.2 O3-δ, and BaZr0.8 Y0.1 Yb0.1 O3-δ exhibited the highest conductivity among the three Y and Yb co-doped samples studied in this work. Graphical abstract: Image 1 Highlights: Improved phase compatibility with NiO by doping BaZrO3 with Yb or Tm. Total doping level in BaZrO3 keeps at 0.2 by co-doping Y and Yb without dopant loss. Higher ionic conductivity of BaZrO3 co-doped with Y and Yb in co-sintered cells.